1999
DOI: 10.1520/gtj11110j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Specimen-Reconstituting Method on the Undrained Response of Sand

Abstract: An experimental study aimed at a direct comparison of the undrained behavior of sand using specimens reconstituted by different techniques is presented. It is shown that at identical initial void ratio and effective stress state, the moist-tamped sand is potentially liquefiable, but in the water-deposited state may even be dilative. Water-deposited specimens are shown to be very uniform in contrast to the large nonuniformities that usually occur on moist tamping, rendering their results questionable from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(24 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…Other researchers have indicated that tests on samples prepared by dry funnel pluviation are more stable and dilatant than those prepared by wet deposition (Benahmed et al, 2004;Canou, 1989). Vaid et al (1999) confirmed this finding and also showed that wet deposition promotes the quicker onset of liquefaction compared to pluviation under water. In their laboratory investigation, Yamamuro et al (2008) concluded that dry pluviation causes the instability of samples as opposed to the method of sedimentation.…”
Section: Introductionsupporting
confidence: 70%
“…Other researchers have indicated that tests on samples prepared by dry funnel pluviation are more stable and dilatant than those prepared by wet deposition (Benahmed et al, 2004;Canou, 1989). Vaid et al (1999) confirmed this finding and also showed that wet deposition promotes the quicker onset of liquefaction compared to pluviation under water. In their laboratory investigation, Yamamuro et al (2008) concluded that dry pluviation causes the instability of samples as opposed to the method of sedimentation.…”
Section: Introductionsupporting
confidence: 70%
“…Laboratory observations have consistently found that two specimens of a sand prepared by different reconstitution methods to the same density may display quite different responses to applied monotonic loading under otherwise similar conditions (e.g., Arthur and Menzies 1972;Oda 1972;Miura and Toki 1982;Vaid et al 1999;Yang et al 2008). The differences are thought to be linked to the different fabrics of the specimens formed by the different methods, which can be defined as the spatial arrangement of sand particles and associated voids (Brewer 1964;Oda and Iwashita 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the choice of a proper sample preparation method is essential to determine the 9 instability potential of sandy soils. The sedimentation deposition method tends to reproduce well field performance as shown by Chaney et al (1999). In this present study, dry funnel pluviation was used as a sample preparation method in order to replicate the soil conditions at the field.…”
Section: Experimental Program Preparation Methodsmentioning
confidence: 96%